A Systematic Review of Models Used and Preferences for Continuing Education and Continuing Professional Development of Pharmacists - Micallef, Ricarda (Pharmacy (Basel), 2019)
Continuing Education (CE) or Continuing Professional Development (CPD) are used by pharmacists globally to maintain up-to-date knowledge and skills throughout their careers. The primary aim of this study was to identify the formats or models used by pharmacists for CE and CPD globally. The secondary aim was to identify preferences of pharmacists, in relation to the variety of formats or models used to fulfil mandatory requirements, in order to support future planning of lifelong learning events. A systematic review was performed using PubMed, Science Direct, and Web of Science covering a time period from 1995 until March 2018. Searches were conducted in English, with studies on undergraduate studies being excluded. Eighteen papers from an initial search of 4561 were included from 2004 to 2014. All studies focused on pharmacists. Three studies identified face-to-face learning as a preference, with six studies identifying a positive impact of interactive learning. All four identified studies focusing on online provision were linked to CE. One study highlighted the benefits of blended learning. Two studies identified concluded that no one size fits all. A clear structure of event was highlighted in three studies. Three studies highlighted the relevance of topics to practice, and two studies showed the need for opportunities to apply knowledge. Due to the variety of formats and no consistent model, no perfect model or activity has been identified. However, CPD showed increased practice outcomes versus CE. Although an increasing amount of technology is being utilized, face-to-face learning is still preferred. Interactive, multiple-format learning should be used where possible, to reflect preferences of different learners. There is a need for a structured approach to the planning and learning event itself to support CE and CPD.